2016
DOI: 10.1021/acsnano.5b04996
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Repair by Circumferential Cell Therapy Using Magnetic Nanoparticles and Tailored Magnets

Abstract: Cardiovascular disease is often caused by endothelial cell (EC) dysfunction and atherosclerotic plaque formation at predilection sites. Also surgical procedures of plaque removal cause irreversible damage to the EC layer, inducing impairment of vascular function and restenosis. In the current study we have examined a potentially curative approach by radially symmetric re-endothelialization of vessels after their mechanical denudation. For this purpose a combination of nanotechnology with gene and cell therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Among these properties, magnetic and optical properties can be efficiently controlled due to the synergistic effect and coupling effect 3. Especially, heterostructures consisted of noble metal and magnetic NPs, which could make good use of the special plasmonic resonance properties of noble metal counterpart and the unique magnetic properties of magnetic counterpart, have exhibited excellent potential applications in various fields such as multimodal imaging, targeting cancer therapy, and recyclable catalysis 4. Recently, plasmon‐enhanced two‐photon fluorescence (TPF) of Au and Ag NPs exhibit great advantages over conventional one‐photon fluorescent imaging 5.…”
Section: Introductionmentioning
confidence: 99%
“…Among these properties, magnetic and optical properties can be efficiently controlled due to the synergistic effect and coupling effect 3. Especially, heterostructures consisted of noble metal and magnetic NPs, which could make good use of the special plasmonic resonance properties of noble metal counterpart and the unique magnetic properties of magnetic counterpart, have exhibited excellent potential applications in various fields such as multimodal imaging, targeting cancer therapy, and recyclable catalysis 4. Recently, plasmon‐enhanced two‐photon fluorescence (TPF) of Au and Ag NPs exhibit great advantages over conventional one‐photon fluorescent imaging 5.…”
Section: Introductionmentioning
confidence: 99%
“…The use of MNP in combination with various genetic vectors (magnetofection method) has been object of several in vitro and in vivo studies by us 7, 8, 22, 23 and other groups 15, 24, 25. However, gene targeting by MNP, especially after systemic administration in vivo , has proven to be insufficient probably due to low magnetic moments of the single MNP, particle aggregation in the blood, and rapid clearance from the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…The reason might be due to the excessive intensity (>1 T) of the magnetic fields needed to treat tumor cells (Zhang et al, 2016a;Gokduman and Gok, 2020), which will interfere with other normal physiological activities of the body. Complexes of lentiviral vectors and MNPs have been used to re-endothelialize and restore vascular function (Vosen et al, 2016a). Bekhite et al found that SMFs increase cardiomyocyte differentiation of Flk-1 + cells derived from mouse embryonic stem cells via Ca 2+ influx and ROS production (Bekhite et al, 2013).…”
Section: Remanent Magnetization M R Tmentioning
confidence: 99%